Expressive suppression mediates the relation between disordered eating and suicidal ideation. Issue 10 (23rd July 2019) - Ortiz, Shelby; Knauft, Katherine; Smith, April; Kalia, Vrinda
Abstract: Objective: Although disordered eating is robustly associated with suicidal thoughts, it is not well understood why these conditions relate to each other. Emotion dysregulation is a shared risk factor for disordered eating and suicidal thoughts. Individuals with dysregulated emotions struggle to select appropriate strategies to modulate emotions and the strategies they use might explain some of the shared variances. Thus, we examined whether emotion regulation strategies mediated the relationship between disordered eating and suicidal ideation. Method: Adult participants ( N  = 230) completed questionnaires on current disordered eating symptoms, emotion regulation strategies, and current suicidal ideation. Results: Disordered eating symptoms positively associated with suicidal ideation. In addition, expressive suppression mediated the relation between disordered eating symptoms and current suicidal ideation. No relation was found for cognitive reappraisal. Conclusions: The use of expressive suppression as an emotion regulation strategy may be related to increased suicidal ideation in individuals who express concerns about eating.